OPTIMALISASI PELAKU USAHA DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT DESA SUKASARI - Damayanti, Monika; Pahlevi, Rizal; Rahmawati, Rafika (An-Nizam, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) in Sukasari Village requires the right strategy to improve their quality in an increasingly competitive market. One of the approaches adopted is the use of digital branding and marketing as a means of optimizing business actors. This research aims to analyze the role of digital branding and marketing in improving the quality of MSMEs in Sukasari Village. Information was gathered via comprehensive interviews with MSME owners and direct observation of their digital branding and marketing practices. This research also identifies several challenges faced by business actors in implementing digital branding and marketing strategies, including limited knowledge and access to technology. Therefore, strategic recommendations are suggested to overcome these obstacles, such as providing training and technical support for business actors as well as improving digital infrastructure in Sukasari Village. With proper implementation and adequate support, businesses can optimize their potential and compete more effectively in a global market that is increasingly digitally connected.